2020
DOI: 10.1177/2050640619900820
|View full text |Cite
|
Sign up to set email alerts
|

Novel reliability criteria for controlled attenuation parameter assessments for non‐invasive evaluation of hepatic steatosis

Abstract: Background There is conflicting evidence regarding reliability criteria for the controlled attenuation parameter (CAP; a marker for hepatic steatosis [HS]). Thus, we assessed the diagnostic performance of CAP according to different reliability criteria based on real-world data from an academic centre. Methods Patients undergoing measurement of CAP and liver biopsy (±6 months) at the Medical University of Vienna were included. HS was assessed according to SAF score. Results In total 319 patients were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…The measurements were carried out after patients fasted for a period of at least 3 h. The M- and XL-probes were chosen as suggested by the manufacturer or based on the expertise of the hepatologist. Patients were instructed to lie in a dorsal position with the right arm in abduction, and measurements were performed on the right lobe of the liver through the intercostal spaces [ 17 ]. The reliability of LSM was defined in accordance with previously established criteria [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were carried out after patients fasted for a period of at least 3 h. The M- and XL-probes were chosen as suggested by the manufacturer or based on the expertise of the hepatologist. Patients were instructed to lie in a dorsal position with the right arm in abduction, and measurements were performed on the right lobe of the liver through the intercostal spaces [ 17 ]. The reliability of LSM was defined in accordance with previously established criteria [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the minimum and maximum of all the optimal MRI PDFF thresholds reported in the cited studies to identify steatosis grades � 1, � 2 and �3 were [min max] = [3.7% 12.5%], [11.3% 17.4%], and [16.7% 26.5%] respectively [16][17][18][19]21,41,42]. The minimum and maximum of all the CAP thresholds reported in the cited studies to identify steatosis grades � 1, � 2 and �3 were [min max] = 236 dB/m 331 dB/m], [256 dB/m 361dB/m], and [283 dB/m 344 dB/m] respectively [29][30][31][32][33][34][35]41,42]. Further studies are required to validate the applicability of specific optimal thresholds for identifying different steatosis grades.…”
Section: Plos Onementioning
confidence: 99%
“…The measurement is performed using the ultrasound-based technology FibroScan 1 [Echosens, Paris, France] [28]. Although CAP has been shown to work well for the detection of significant hepatic steatosis, results from different studies suggest discordance between CAP and histology scores, and in particular, the diagnostic accuracy is impaired by an increased BMI as well as presence of NASH, NAFLD, and Type 2 diabetes [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has set the IQR upper limit at 30 dB/m [ 8 ], while another study found no difference in CAP performance when the IQR was ≥30 dB/m or ≥40 dB/m [ 20 ]. A recently published study demonstrated that CAP-IQR/M < 0.3 as a quality criterion improves accuracy and feasibility of CAP measurements, performing better than the IQR < 40 dB/m criterion [ 21 ].…”
Section: Controlled Attenuation Parameter (Cap): Technical Datamentioning
confidence: 99%